Patients with moderate Alzheimer’s disease engage in verbal reminiscence with the support of a computer-aided program: a pilot study - Lancioni, Giulio E.; Singh, Nirbhay N.; O’Reilly, Mark F.; Sigafoos, Jeff; D’Amico, Fiora; Ferlisi, Gabriele; Denitto, Floriana; De Vanna, Floriana; Belardinelli, Marta Olivetti (Frontiers in Aging Neuroscience, 2015)
This study focused on the assessment of a program recently developed for helping patients with moderate Alzheimer’s disease engage in computer-mediated verbal reminiscence (Lancioni et al., 2014a). Sixteen participants were involved in the study. Six of them used the original program version with the computer showing a virtual partner posing questions and providing attention and guidance. The other 10 used a slightly modified program version with the computer presenting photos and videos and providing encouragements to talk as well as attention and guidance. Participants were exposed to brief program sessions individually. The results showed that 15 participants (five of those using the first version and all of those using the second version) had a clear and lasting increase in verbal engagement/reminiscence during the intervention sessions with the program. Those 15 participants had mean percentages of intervals with verbal engagement/reminiscence below 10 during baseline and between about 45 and 75 during the intervention. The results’ implications and the need for new research were discussed.